Glycogen Synthase Kinase 3β in the Ventral Hippocampus is Important for Cocaine Reward and Object Location Memory. (15th January 2020) - Barr, Jeffrey L.; Shi, Xiangdang; Zaykaner, Michael; Unterwald, Ellen M.
Highlights: Knockdown of GSK3β in the ventral hippocampus diminished acquisition of cocaine conditioned place preference. Acquisition of place preference for morphine was not altered by knockdown of ventral hippocampal GSK3β. Object location memory but not novel object recognition was impaired by knockdown of ventral hippocampal GSK3β. Abstract: The ventral hippocampus is a component of the neural circuitry involved with context-associated memory for reward and generation of appropriate behavioral responses to context. Glycogen synthase kinase 3 beta (GSK3β) has been linked to the maintenance of synaptic plasticity, contextual memory retrieval, and is involved in the reconsolidation of cocaine-associated contextual memory. In this study, the effects of targeted downregulation of GSK3β in the ventral hippocampus were examined on a series of behavioral tests for assessing drug reward-context association and non-reward related memory. The Cre/loxP site-specific recombination system was used to knockdown GSK3β through bilateral stereotaxic delivery of an adeno-associated virus expressing Cre-recombinase (AAV-Cre) into the ventral hippocampus of adult mice homozygous for a floxed GSK3β allele. GSK3β floxed mice injected with AAV-Cre had a loss of 56–75% of GSK3β in the ventral hippocampus and displayed diminished development of cocaine conditioned place preference, but not morphine place preference as compared with wild-type mice injected with AAV-Cre or GSK3β floxed mice injected with a control virus, AAV-GFP. Impaired object location memory was observed in mice with GSK3β downregulation in the ventral hippocampus, but novel object recognition remained intact. These results indicate that GSK3β signaling in the ventral hippocampus is differentially involved in the formation of place-drug reward association dependent upon drug class. Additionally, ventral hippocampal GSK3β signaling is important in detection of discrete spatial cues, but not recognition memory for objects.